Beyond Antibiotics? - LE Nicolle (Canadian Journal of Infectious Diseases and Medical Microbiology)
The AMMI Canada meeting in March 2006 hosted a symposium exploring the potential alternatives to antibiotics for the prevention and treatment of infection. Four papers summarizing talks from that session are published in this issue of the Journal (1-4). These reviews address the scientific underpinnings for a number of proposed concepts, and summarize the current status of clinical use. The approaches - probiotics, bacteriophage therapy, and manipulation of innate immunity - are all intriguing but are still removed from immediate practical applications.